IDENTIFYING THE CAUSES OF INFERTILITY THROUGH IMAGING PROCEDURES: A CASE REPORT - Farida, Rizkha; Hidayat, Evelyn Christina (International Journal of Radiology and Imaging, 2025)
Infertility is the fifth highest serious global health issue affecting both males and females. Globally, more than 186 million people suffer from infertility and the number has increased considerably. A diagnosis of infertility is typically made when a couple fails to achieve pregnancy after one year of regular, unprotected intercourse. A 23-year-old nulliparous woman presented with a chief complaint of infertility for the past 2 years. She also complained of abdominal pain for the past 6 months. Ultrasonography (USG) revealed a left ovarian cyst measuring 4.12 cm. Hysterosalpingography (HSG) showed bilateral hydrosalpinx with bilateral patent fallopian tubes. Her husband has not undergone a male infertility evaluation. Problems associated with infertility include abnormal follicle growth, structural malformations, fallopian tube impairment, and uterine defects. The most common imaging test for evaluating tubal patency is HSG, and ultrasound can further assist in visualizing the uterus and surrounding adnexal regions. In this case, USG revealed an ovarian cyst. Cysts affect fertility based on their size, type, and quantity. HSG allows imaging of the uterus and fallopian tubes. Blockage of fallopian tube can inhibit reproduction. The worst manifestation is hydrosalpinx, characterized by fluid filled dilation of the fallopian tube caused by a blockage at distal part, which impairs the fertilization process. Symptoms of hydrosalpinx can be preceded by abdominal pain, similar to this patient’s complaint. Diagnostic imaging plays a vital role in assessing infertility, and selecting the most suitable imaging method is crucial because the results guide the direction of patient treatment.